PERANCANGAN MEDIA PROMOSI AMITIE SWEETS BOUTIQUE SEBAGAI UPAYA PENINGKATAN BRAND AWARENESS - Then Michael; Lisana Lisana; Tyrza Adelia (Perpustakaan Universitas Surabaya, 2020)
Brand awareness is about how far someone can remember a brand in its category. Amitie Sweets Boutique is a chocolate and cake company established in 2013. Products offered include chocolates, cookies, cakes, tarts, and hampers, which are homemade and custom order. Based on Amitie customer data from 2014 to 2017, on average there are approximately 10 customers per month. According to a survey conducted, only 35% of people who know the brand that called Amitie, and 60% of them know Amitie through friend referral. The owner of Amitie has plans to further develop their business, so that the brand becomes widely known and always be consumer͛Ɛdestination, and can reach other areas. Currently, Amitie actively promotes their products through social media (Instagram), so thus there are more room to maximize their brand-building efforts. According to Aaker, D (2014) the company in its brand building efforts should be able to use digital promotion media such as website, video, and social media. The solutions for the problems faced by Amitie is to improve the way of promotion Amitie with the design of promotional media both digital and print. Stages of designing Amitie promotional media begins with an analysis of promotional media, analysis of Amitie, and SWOT comparison with similar competitors. Promotion media implemented include company profile website, product video, and brochure. The overall design of the promotional media was created by using readily available software such as Adobe Photoshop, Adobe Premiere, Adobe Illustrator, and Visual Studio Code. The result of the promotional media created has passed the design and testing stages. Based on the results of the trial, it was found that the design of Amitie promotional media has increased the brand awareness of Amitie to the wider target market.